Lower secondary science teaching and learning: Teachers' characteristics and perspectives: Summary report - George, June M. (School of Education, UWI, St. Augustine, 2004)
This is a summary of the findings of a study that sought to gain a fuller understanding of the characteristics of the teachers engaged in teaching science at the lower secondary level in schools in Trinidad and Tobago, as well as some of the perspectives of these teachers with respect to the teaching of lower secondary science. It also sought to determine what gains, if any, had been made in the eight-year period since a study with somewhat similar aims had been undertaken, with respect to the quality of the provision for the teaching and learning of science at this level
Keywords: Lower secondary education; Science teachers; Science education; Secondary school teachers; Teacher characteristics; Teacher attitudes; Trinidad and Tobago